Pelatihan Pengelasan dan Service Ringan Sistem Pendingin Refrigerasi Serta AC di Kepulauan Seribu - Aries Abbas; Denny Prumanto; Nurkim Nurkim (Universitas Pahlawan Tuanku Tambusai, 2023)
Community service activities carried out in the Thousand Islands by the P2M Mechanical Engineering team at the Faculty of Engineering UNKRIS together with partners, namely youth youth organizations and Al-Islah Islamic boarding school students with lecture training methods, hands-on practice and evaluations carried out for 3 (three) days. The purpose of this activity is to realize the development of community skills, especially youth youth and Islamic boarding school students to support economic activities and provide solutions for the majority of the community as fishermen to overcome obstacles both to boat cooling devices and also damage to air conditioners which so far have relied on experts from land. The results of the training are: (1) participants can apply the results of welding by making nameplates with the welding process (2) can apply the results of maintenance of the Split wall type cooling system by carrying out maintenance and inspection processes and cleaning of indoor and outdoor parts. This activity has a positive impact on increasing the competence and expertise of participants, and it is hoped that every year there will be training activities like this.